Zinc as a non-hormonal contraceptive: an alternative to the copper intrauterine device (IUD). Issue 4 (24th August 2022) - Shankie-Williams, K N; Lindsay, L A; Murphy, C R; Dowland, S N
Abstract : In brief: The many side effects of current contraceptives leave a large proportion of women without adequate protection. This study shows that zinc, a highly physiologically compatible metal, provides effective long-acting reversible contraception in rats, without requiring the use of hormones. Abstract: Long-acting and reversible contraceptives (LARC) are the most widely used form of female contraception worldwide; however, they have significant side effects that often result in early removal. Most LARCs are hormonal, but the use of exogenous hormones is not suitable for all women and causes side effects in many others. The copper IUD (CuIUD) is the only non-hormonal LARC, but a large proportion of users suffer severe side effects. This study proposes the use of zinc as a suitable alternative to the CuIUD. A rat intrauterine device (IUD) model was established to test the efficacy of a zinc IUD (ZnIUD) against a CuIUD. The IUD was surgically implanted into one uterine horn while the other remained untreated. Both the ZnIUD and CuIUD resulted in zero implantation sites which were significantly fewer compared to non-treated horns. Histological assessment revealed damage and inflammation in the endometrium of CuIUD-treated horns but only minor epithelial changes in ZnIUD-treated horns. This suggests ZnIUDs may not share the side effect profile of the CuIUD. To test the long-term efficacy of the ZnIUD, rats had a ZnIUD surgically implanted into both horns and cohoused with males for 3 months. These rats mated regularly but did not get pregnant, confirming long-term effectiveness. Reversibility of the ZnIUD was also established, as removal of the ZnIUD after 3 months resulted in no significant difference in the number of implantation sites between treated and untreated horns. This study demonstrated the contraceptive efficacy of zinc and its potential as a LARC.